IDENTIFIKASI KANDUNGAN FITOKIMIA TUMBUHAN PIDADA (Sonneratia Caseolaris) DARI HUTAN MANGROVE - Leli Srinengri; Henny Arryati (Universitas Lambung Mangkurat, 2020)
Mangrove plants have the potential as efficacious drugs, one of the plants in question is Pidada (Sonneratia caseolaris). All parts of the Pidada plant can be used as medicine. The purpose of this study was to identify the content of Pidada active compounds qualitatively. The research method is using phytochemical test. The results obtained from the Pidada plant phytochemical test are the most active chemical compounds found in Steroid compounds which are found in all parts of the plant (roots, stems, leaves and skin). Saponin compounds are found after Steroids, which are found in the roots, leaves and skin of Pidada plants. Alkaloids are only found in the Pidada roots. Triterpenoids are found in all four parts of the Pidada plant. Flavonoids are found only on the skin of Pidada. Quinon is found only on the roots and skin of Pidada.Keywords: Phytochemical Test, Pidada, Steroid, Flavonoid